Workers' exposure to electric fields during the task 'maintenance of an operating device of circuit breaker from a service platform' at 110-kV substations. Issue 1 (2nd January 2019) - Korpinen, Leena; Pääkkönen, Rauno
Abstract : The objective of the study was to investigate occupational exposure to electric fields during the task 'maintenance of an operating device of circuit breaker from a service platform' at 110-kV substations. The aim was also to compare the results to Directive 2013/35/EU. At 16 substations, 255 electric field measurements were performed. The highest mean value of the electric fields was 9.6 kV⋅m −1 . At 63% of substations the maximum values were over 10.0 kV⋅m −1, and at 31% of the substations the 75th percentiles were over 10.0 kV⋅m −1, which is the low action level (AL) according to Directive 2013/35/EU. All measured values were below the high AL (20.0 kV⋅m −1 ). In the future, it is important to take into account that the measurements were only taken at Finnish 110-kV substations; therefore, it is not possible to generalize these results to other countries and different types of substations.